Assessing the efficacy of myrothamnus flabellifolius (mufandichimuka) in controlling coccidiosis in indigenous chickens - Mupondi, Edith Samantha (BUSE, 2024)
Eimeria, a codiosis causing bacteria leads to huge economic losses to the poultry farming industry. To mitigate the challenge there has been conventional formulations as an endeavour to boost chicken growth rate and health in general. To date there are several challenges being faced by poultry farmers because of the conventional codiostat available, which can face bacterial resistance from the virulent Eimeria. The study assessed the qualitative and quantitative bioactive chemicals in Myrothamnus flabellifolius (Mufandichimuka) aqueous and acetone extract. It also investigated the effectiveness of the plant as a codiostat. Lastly, there was M. flabellifolius codiostat formulation and packagingand packagingdevelopment and packaging and packaging. For the qualitative analysis, phytochemical compounds were identified using standard screening tests, including tests for phenols, tannins, saponins, glycosides, alkaloids, flavonoids, and terpenoids. The data was analysed using descriptive statistics to provide a summary of the characteristics of the coccidial compounds. This included measures such as mean and standard deviation. Also, the results were subjected to an independent samples t-test. The qualitative results revealed that, phenols, tannins, saponins, glycosides, alkaloids, flavonoids, and terpenoids were present in the plant extracts. Furthermore, quantitative analysis, quantified phenols, flavonoids, tannins, saponins and alkaloids. Overall, the results indicate that the acetone solvent was more effective in extracting these phytochemical compounds from the plant material compared to the hot water solvent. A multi-faceted approach using ethanol, methanol, and hydro distillation, combined with advanced processing techniques, can maximize the extraction efficiency of M. flabellifolius, ensuring the retrieval of its diverse bioactive compounds for various therapeutic applications. To address the issue of level of effectiveness of the plant’s extracts, phytochemicals were quantified, and birds' growth rates, invitro assays, and mortality rates were studied. To analyze the growth rate, all the birds used in the study were weighed every 7 days. The reduction of oocyst counts, focused on the faecal oocyst concentration reduction rate. Birds were observed for mortality, counting total deaths post inoculation. The data for weight gain was analyzed using one way ANOVA. Also, the weight gain was subjected to Bonferroni post-hoc test for pairwise comparisons. The results for oocyst reduction rate were expressed as percentages. The mortality rates were expressed in percentages. The results indicate that the M. flabellifolius treatment group had the highest mean weight gain at day 42. Group which received the M. flabellifolius treatment, also exhibited lower mortality rates compared to the untreated group. Lastly, the data suggests that the two treatment interventions, particularly the Coccidiostat and ESB3 combination, had a significant positive impact on the oocyst count reduction, resulting in a much more substantial and sustained increase compared to the control group. Overall, this study demonstrated that M. flabellifolius can reduce coccidiosis infected poultry mortality, reduce oocyst count and improve the growth weight. The development and packaging and packaging of the plant codiostat, involved, labelling, packaging material, packaging design, packaging, quality control and stability testing.
Keywords: Coccidiosis; Phytochemical; Coccidiosis management; Myrothamnus flabellifolius; Aqueous extract; Solvent extract; Level of effectiveness; Natural remedies; Traditional medicine; Veterinary medicine.